Pemikiran Ahmad Muhamad Mustain Nasoha Tentang Etika Politik Hukum dalam Pemberantasan Korupsi di Indonesia - Ahmad Muhammad Mustain Nasoha; Yahya Ayyasy Alghossan; Wildan Naufal Ghoni; Ratna Rizqian; Naila Izza Nafiisah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the crucial role of political ethics in anti-corruption efforts in Indonesia, focusing on Pancasila as the moral and philosophical foundation (Nasoha et al., 2024; Atqiya & Nasoha, 2024). Through a qualitative literature review, the research reveals that weaknesses in political ethics significantly contribute to corrupt practices among elites and state institutions. The study highlights that corruption often stems from a lack of adherence to ethical standards within the political system. Therefore, strengthening political ethics is essential to preventing corruption. The principles of justice, accountability, and public responsibility are critical to this effort, ensuring that government actions align with ethical values. Pancasila’s core values, especially social justice and gotong royong (mutual cooperation), provide a solid moral framework for fostering a transparent, fair, and integrated government system. By embedding these values into political practice, Indonesia can strengthen its anti-corruption efforts, improve public trust, and promote a more just and accountable political environment.